Effect of Different Fencing Regimes on Community Structure of Perennial Plant Species in Cholistan Desert, Pakistan - Khan, Muhammad Idrees; Habib-Ur-Rehman; Ahmed, Manzoor; Asghar, Farrukh; Abdul Latif; Ejaz ul Haq; Nadeem, Muskan; Sikandar M Zulqarnain; Naz, Nargis; Akhtar, Hassan (Indus Journal of Bioscience Research, 2025)
The present study was conducted to analyze the effect of different fencing regimes on a community structure of perennial plant species in Cholistan desert. Major sites include Derawar Fort (Biodiversity Park IUB), Mauj Garh Fort (Livestock Farm) And Lal Suhanra National Park (Sheikh Mohammed Bin Zayed Al-Nahyan Conservation and Breeding Center). In each site, thirty-three quadrats measuring 10 x 10 m2 are laid out at random i-e., eleven quadrats at each sub sites (sand dune, inter dune and clayey land). During the study the parameter which we covered are density, relative density, relative frequency, cover, relative cover, importance value index and diversity index. After the completion of the study 31 families and 57 species are reported in all three sites. Ochthochloa compressa, Suaeda fruticose and Lasiurus scindicus showed very high values of relative density, relative frequency, relative cover and importance value. Cenchrus ciliaris, Cymbopogon jwarancusa followed by Haloxylon salicarnicum have moderate while Ziziphus nummularia, Salvadora oleiodes, Aristida hystricula, Calotropis procera and Heliotropium crispum have very low values of phytosociology parameters. The average of Diversity index of all species are found at all three sites was (0.8009822). Overall selected three sites play an important role in the conservation of many native species of desert that are otherwise facing multiple biotic abiotic and anthropogenic factors.